Cancer morbidity in rheumatoid arthritis. Issue 2 (April 1984) - Prior, P; Symmons, D P; Hawkins, C F; Scott, D L; Brown, R
Abstract : A consecutive series of 489 patients with rheumatoid arthritis seen at the centre was studied to determine their cancer morbidity. Overall the 36 cancers diagnosed in the series between 1964 and 1981 were not significantly in excess of the expected number, but there was a highly significant excess of tumours of the reticuloendothelial system. The excess was mainly due to 6 observed cases of lymphoma. We conclude that there is a highly significant association between rheumatoid arthritis and the subsequent development of lymphoproliferative malignancy in this series.